What is the appropriate anticoagulation strategy for thrombotic antiphospholipid syndrome?. (28th February 2020) - Arachchillage, Deepa R. J.; Laffan, Mike
Summary: Antiphospholipid syndrome (APS) is an autoimmune prothrombotic disorder mediated by a heterogeneous group of autoantibodies collectively known as antiphospholipid antibodies (aPL). They include lupus anticoagulant (LA), IgG and IgM anticardiolipin antibodies (aCL) and anti‐β2‐glycoprotein I (anti‐β2GPI) antibodies. It has been shown that those patients with all three aPL (triple positive) are at highest risk of both a first thrombotic event and of a recurrence, despite anticoagulation. In response to publication of a meta‐analysis and a randomised controlled trial assessing the safety and efficacy of rivaroxaban versus warfarin in triple‐positive APS with venous and/or arterial thrombosis, the Medicines and Healthcare Products Regulatory Agency (MHRA) and European Medicines Agency (EMA) issued recommendations that direct‐acting oral anticoagulant (DOACs) should not be used for secondary prevention of thrombosis in all APS patients (although they did draw specific attention to the high risk of triple‐positive patients). As there is less evidence for patients with single‐ or dual‐positive patients with APS, this may be an over‐interpretation of the data. In this review, we explore the available evidence on safety and efficacy of DOACs in thrombotic APS, the problem of detecting LA while on DOAC, and provide some practical guidance for managing this problem.